2011
DOI: 10.1039/c0cp02482a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid-assisted carboxylation of amines by CO2: a mechanistic consideration

Abstract: The catalytic roles of ionic liquids (ILs) in the syntheses of 1,3-disubstituted ureas from the carboxylation of amines by CO(2) were experimentally and theoretically investigated. The carboxylation reaction of n-butylamine was greatly facilitated by the presence of an IL and the catalytic activity of the IL was strongly affected by the nucleophilicity of the anion. Computational study on the mechanistic aspects of the carboxylation with methylamine with or without the presence of an IL, 1-ethyl-3-methylimidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…[46] Surprisingly, the CDF in Figure 3 B clearly shows that the closer the solute is to the cation, the less bent it is, as for the lower C(CO 2 )–C2 distances there are no entries corresponding to lower O–C–O angles of the solute. Thus, instead of cooperation, competition is indicated between the anion and the cation for interacting with the CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[46] Surprisingly, the CDF in Figure 3 B clearly shows that the closer the solute is to the cation, the less bent it is, as for the lower C(CO 2 )–C2 distances there are no entries corresponding to lower O–C–O angles of the solute. Thus, instead of cooperation, competition is indicated between the anion and the cation for interacting with the CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years the direct synthesis of substituted ureas has been accomplished with the non toxic and cheap carbon dioxide in the presence of different catalysts and dehydrating agents to increase the yield of reaction [39][40][41][42]. Ionic liquids in conjunction with a base (CsOH) or transition metal (Fe, Co, Ni, Cu, Zn) acetates were also employed as reaction medium and catalysts to obtain 1,3-disubstituted ureas in good yield [43][44][45][46]. However, most catalysts can be reused no more than 3-4 times.…”
Section: Introductionmentioning
confidence: 99%
“…The product yield increased in the following order: dimethyl sulfoxide (DMSO) < CH 3 CN < N,N-dimethylformamide (DMF) < 1-methyl-2-pyrrolidinone (NMP) ( Table 1, entries 5,[10][11][12]. This corresponded with the order of CO 2 solubility in these solvents (expressed as Henry's constant), DMSO (12.67) > CH 3 CN (9.049) > DMF (7.966) > NMP (7.61) [41]. Based on the CO 2 solubility in various solvents being expressed as Henry's constants, it was concluded that the yield of benzothiazolone increased as Henry's constant decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl-substituted lower reactivity, and the yields of the substituted substrates with neither electron-withdrawing groups nor electron-donating groups were also lower than the model reaction. Based on previous reports and the experimental results [28,33,41,42,45], a probable catalytic cycle was proposed for the reaction of 2-aminothiophenols with CO 2 to benzothiazolones using DBN as a catalyst, as depicted in Scheme 2. Firstly, CO 2 could react with DBN to form the key carbamate Based on previous reports and the experimental results [28,33,41,42,45] …”
mentioning
confidence: 99%